2011
DOI: 10.1111/j.1471-0528.2011.03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse perinatal outcomes with antithyroid treatment during pregnancy: a nationwide population-based study

Abstract: Objective To compare, using two large nationwide populationbased data sets, the risk of adverse pregnancy outcomes (low birthweight [LBW], preterm birth, small for gestational age [SGA] and congenital anomalies) among pregnant women with hyperthyroidism classified into three groups: receiving propylthiouracil (PTU) treatment during pregnancy, receiving methimazole/carbimazole (MMI) treatment, and no antithyroid treatment during pregnancy.Design A matched case-control study.Setting Taiwan.Sample A total of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 52 publications
3
65
2
3
Order By: Relevance
“…Overall, the defects were less severe than the MMI/CMZassociated defects (60), and they consisted of face and neck malformations (preauricular sinus and cysts), and urinary tract malformations (confined to boys). Some uncertainty has existed in this area of research, because some investigators found no association between ATD use in pregnancy and birth defects (61,62,63,64). As recently reviewed in detail (65), the cause for the negative findings likely resides with the methods used in the studies.…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 96%
“…Overall, the defects were less severe than the MMI/CMZassociated defects (60), and they consisted of face and neck malformations (preauricular sinus and cysts), and urinary tract malformations (confined to boys). Some uncertainty has existed in this area of research, because some investigators found no association between ATD use in pregnancy and birth defects (61,62,63,64). As recently reviewed in detail (65), the cause for the negative findings likely resides with the methods used in the studies.…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 96%
“…3 Because PTU has (rarely) been associated with liver failure in pregnant women, 5, 57 current guidelines recommend switching to MMI after the first trimester. 5,26 Suggestion:…”
Section: Question 5: Do Maternal Atds Infl Uence the Newborn's Presenmentioning
confidence: 99%
“…[1][2][3][4] The prevalence of transient GD in infants born to these mothers is uncertain, varying from 1.5% to 2.5% [5][6][7] up to 20.0% in observational cohort studies. [7][8][9] The causative antibodies in GD, thyroid-stimulating hormone (TSH) receptor antibodies (TRAb), belong to the immunoglobulin G class and freely cross the placenta, particularly during the second half of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…After this, more cases were published including, now also, more severe birth defects leading to the term methimazole/carbimazole embryopathy (7,8), as described in several reviews (9,15). Still, some studies have been negative (16,17), and until recently, the additional risk of birth defects after early pregnancy use of MMI/CMZ was considered to be very low (2,3). PTU was considered not to be teratogenic (2,3), even if some non-human studies were positive (18,19).…”
Section: Introductionmentioning
confidence: 99%